Eco Airport Design: Rancangan Gedung Terminal Ramah Lingkungan pada Bandar Udara - Suryan, Viktor; Amalia, Direstu; Martadinata, M. Indra; Septiani, Virma; Nurfitri, Meta Amalia; Silitonga, Evandri; Chandra, Putu Wisnu Ardia (Universitas Batanghari Jambi, 2024)
Increasing awareness of the importance of environmental conservation has encouraged the development of eco-design concepts in various fields, including air transportation infrastructure. The main focus of this research is to propose an eco-friendly terminal building design for airports using the Eco Airport Design approach. The research will involve case studies of specific airports to investigate the potential and challenges of applying eco-design principles in airport terminals. The research methods used will include observation, environmental data analysis, and the study of related literature. This research aims to develop design guidelines and recommendations that promote energy efficiency, waste reduction, use of eco-friendly materials, layouts that utilize natural air and light, and improve the environmental quality around the airport. The results of this research are expected to significantly contribute to environmental protection efforts in the context of air transportation infrastructure, particularly airport design for tertiary categories or those serving up to one million passengers per year.